Protective Effects of Salivary Factors in Dental Caries in Diabetic Patients of Pakistan. (24th June 2012) - Jawed, Muhammad; Khan, Rashid N.; Shahid, Syed M.; Azhar, Abid
Abstract : Salivary factors have been studied for their effects on the process of dental caries in patients of diabetes mellitus type 2. In this study, protective role of salivary pH, salivary flow rate, and salivary calcium is assessed in the patients of diabetes mellitus type 2 with dental caries. The samples of saliva were collected from 400 patients of diabetes mellitus type 2 and 300 age- and sex- matched controls after getting informed consent. All the subjects were classified into four groups according to age. The severity of dental caries was counted by decayed, missed, and filled teeth (DMFT) score. The salivary pH, flow rate, and calcium levels were found to be low in patients as compared to controls. The levels of fasting blood sugar, HbA1c, and DMFT score were found to be significantly high in patients than controls. The glycemic factors were significantly correlated with salivary factors indicating their influence on progression of caries in diabetes. On the basis of findings, it is concluded that the suitable salivary pH and flow rate may be regarded as main protective factors against dental caries in diabetes. Optimum level of salivary calcium may be responsible for continuous supply of calcium to arrest the demineralization and help reduce the occurrence of dental caries.